A practical guide to the histology of the mouse - Scudamore, Cheryl L. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2013)
A Practical Guide to the Histology of the Mouse provides a full-colour atlas of mouse histology. Mouse models of disease are used extensively in biomedical research with many hundreds of new models being generated each year. Complete phenotypic analysis of all of these models can benefit from histologic review of the tissues. This book is aimed at veterinary and medical pathologists who are unfamiliar with mouse tissues and scientists who wish to evaluate their own mouse models. It provides practical guidance on the collection, sampling and analysis of mouse tissue samp.
Necropsy of the mouse -- Practical approaches to reviewing and recording pathology data -- Gastrointestinal system -- Cardiovascular system -- Urinary system -- Reproductive system -- Endocrine system -- Nervous system -- Lymphoid and haematopoietic system -- Integument and adipose tissue -- The respiratory system -- Special senses -- Musculoskeletal.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Mice as laboratory animals; Mice -- Physiology; Mice -- anatomy & histology; Mice -- physiology; Animals, Laboratory; Histocytological Preparation Techniques; Specimen Handling; Histology -- Atlases; Mice -- Embryology -- Atlases; Mice -- Histology -- Atlases; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Mice as laboratory animals; Mice -- Physiology; Electronic books